Modern Approaches to MRI Diagnostics of Forefoot Pathology (Literature Review) - Radchenko, K.A.; Haiko, O.G.; Luchko, R.V. (TERRA ORTHOPAEDICA, 2023)
Summary. The problem of pain in the forefoot is extremely relevant in the medical and social spheres. Diseases and injuries of the foot account for 6-12% of the total number of all injuries and diseases of the musculoskeletal system. The article is devoted to the main diagnostic capabilities of magnetic resonance imaging (MRI) for pathology of the forefoot, determining the indications for examination of the patient and protocols for examining the foot.